Regulating flowering pattern to improve assimilate translocation efficiency and pod yield of groundnut (Arachis hypogaea L.): Regulating flowering pattern to improve assimilate translocation efficiency and pod yield of groundnut (Arachis hypogaea L.) - C HARISUDAN; S SRINIVASAN; N THAVAPRAKAASH; K SUBRAHMANIYAN (Journal of Oilseeds Research, 2023)
Groundnut is an indeterminate crop wherein vegetative and reproductive phases overlap, resulting in immature pods and poor pod yield. Field experiment was conducted to reduce later formed flowers and pod yield. The results of experiment revealed that foliar spray of late formed flower arresting formulation significantly reduced late formed flowers and recorded higher groundnut pod yield.